Photography in the Middle: Dispatches on Media Ecologies and Aesthetics - Coley, Rob (punctum books, 2016)
It's easy to forget there's a war on when the front line is everywhere encrypted in plain sight. Gathered in this book's several chapters are dispatches on the role of photography in a War Universe, a space and time in which photographers such as Hilla Becher, Don McCullin and Eadweard Muybridge exist only insofar as they are a mark of possession, in the sway of larger forces. These photographers are conceptual personae that collectively fabulate a different kind of photography, a paraphotography in which the camera produces negative abyssal flashes or 'endarkenment.' In his Vietnam War memoir, Dispatches, Michael Herr imagines a 'dropped camera' receiving 'jumping and falling' images, images which capture the weird indivisibility of medium and mediated in a time of war. The movies and the war, the photographs and the torn bodies, fused and exchanged. Reporting from the chaos at the middle of things, Herr invokes a kind of writing attuned to this experience. Photography in the Middle, eschewing a high theoretical mode, seeks to exploit the bag of tricks that is the dispatch. The dispatch makes no grand statement about the progress of the war. Cultivating the most perverse implications of its sources, it tries to express what the daily briefing never can. Ports of entry in the script we're given, odd and hasty little glyphs, unhelpful rips in the cover story, dispatches are futile, dark intuitions, an expeditious inefficacy. They are bleak but necessary responses to an indifferent world in which any action whatever has little noticeable effect.